A avaliatividade e o pós-guerra em Home, de Toni Morrison uma abordagem sistêmico-funcional - Santos, Aparecida Araujo dos (2016)
Appraisal is a system to map the resources used to evaluate the social experience, carried out through several lexical-grammatical structures. The aim of this master thesis is to investigate the role of Appraisal on the narrative of suffering of a black Korean War veteran in two chapters of Home by Toni Morrison (2012), a Nobel Prize Laureate in 1993. If peace means the absence of war, this is a state the protagonist of Home - Frank - is unable to experience because he is followed by post-traumatic stress disorder, caused by the war and racial conflicts memories from childhood, during the 1950s segregation, caused by Jim Crow laws and McCarthyism. The narrative discourse analysis from the viewpoint of writer/reader relations reveals some mechanisms by which the narrative "works" on readers, enabling them to "feel with" a certain character and ethically judge his behavior. The survey runs through this literary universe in the light of discourse analysis, which, being trodden by scholars and researchers from socioideological and historical issues, was generally done obscurely, without the understanding support of their linguistic materiality. This study is based on the theoretical and methodological model of Systemic Functional Linguistics (SFL), focusing on the Appraisal, an extension of Interpersonal metafunction of this theory. By the process of metarelation, redundant qualifiers and amplifiers or restrictive components, that is functionally a single assessment, are spread through the sentence or even long parts of a text. The research should answer the following questions: (a) What role does the Appraisal play in Frank‟s character composition? (b) What is the function of metarelation in this process? The novel analysis shows that the resources of Appraisal, running through the text by the metarelation process, contributes to the axiological creation of narration. The research shows some implications for the analysis of the evaluation in the text considering the contextual constraints to the development of relations between writer and reader